The development of ‘ilm tafsir and hadith in Malaysian educational system = Perkembangan ilmu tafsir dan hadis dalam sistem pendidikan Malaysia - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (International Islamic University University Malaysia, 2019)
The development of science of tafsÊr and hadith in Malaysia is quite advanced. However both are not formally established as a discipline of science. The discussion is more towards the science of tafsir and hadith commentary itself rather than studying the problems in society and its solutions from the perspective of Qur’an and Sunnah. Employing qualitative method, this paper aims at studying the experience of Malaysia in the development of science of tafsir and hadith studies, the historical overview and its impact towards educational system and other Islamic institutions, such as Shariah judicial and the financial system. The paper also seeks to identify the challenges and obstacles that might have hindered the progress of developing a more integrated methodology of science of tafsÊr and hadith studies that may offer practical solutions to address the current religious, socio-political and economic problems facing the Muslim society from the Qur’an and hadith perspectives.